The Effect of School Principal Leadership and Teacher Work Motivation on Teacher Creativity in Seram Barat District - Yolanda Gysberthus; T. G. Ratumanan; S. Rumfot (International Journal of Education, Information Technology, and Others, 2022)
This study aims to determine the effect of principal leadership and teacher work motivation on the creativity of high school teachers in West Seram sub-district. The research method used in this study is a quantitative study with a correlational approach conducted on 5 high schools in West Seram sub-district with a population of 133. The sample was taken by proportional random sampling technique, and with the Slovin formula obtained a sample of 100 people. This study resulted in the following conclusions: 1) There is a positive and significant relationship between the principal's leadership on teacher creativity with an R value of 0.551, the regression line equation shows that = 75.337 + 0.350 with a tcount > ttable or 75.337 > 1.661 this is evidenced by consulting the R value with the coefficient table for the r value. other than that the regression line equation shows that = 2.381 + 0.859. 2) There is a positive and significant relationship between teacher work motivation and teacher creativity with a value of R = 0.869, forming a regression line = 28.880 + 0.749 and obtained tcount > ttable or 28,880 > 1.661. 3) Based on the significance test, the significance test was obtained with Fcount = 164.132 while Ftable with a significant level = 0.05 dk = 100 – 2 = 98 , then Ftable value = 3.938 It turns out that Fcount > Ftable or 164.132 > 3.938 then Ho rejected and H1 accepted means significant or there is an influence of principal leadership and teacher work motivation on teacher creativity.